The Effect of Local Melatonin Application on Bone Fracture Healing in Rat Tibias - Tanrisever, Murat; Tekin, Bahar; Can, Umit Koray; Istek, Ozmen; Ozcan, Erhan Cahit; Ozercan, Ibrahim H.; Dundar, Serkan (Mdpi, 2025)
Background and Objectives: This study aimed to histologically evaluate the effects of local melatonin application at different doses on bone fracture healing. Materials and Methods: Thirty rats were divided into three groups, with ten rats in each group. In the control group (n = 10), a fracture line was created in the tibial bones, and fracture osteosynthesis was performed without any additional procedure. In the local melatonin dose 1 (MLT D-1) group (n = 10), a fracture line was created in the tibial bones, and 1.2 mg of lyophilized powder melatonin was applied locally before fracture osteosynthesis. In the local melatonin dose 2 (MLT D-2) group (n = 10), a fracture line was created in the tibial bones, and 3 mg of lyophilized powder melatonin was applied locally before fracture osteosynthesis. After a 12-week healing period, all subjects were sacrificed, and tibial bones were collected for histomorphometric analysis. Results: The percentage of bone formation was significantly higher in the MLT D-1 and MLT D-2 groups than in the control group. There was no statistically significant difference between the MLT D-1 and MLT D-2 groups. Conclusions: In conclusion, the study demonstrated that local melatonin application supports bone fracture by increasing bone formation, although different doses of melatonin did not lead to significant variations in fracture healing.
Keywords: bone formation; fracture healing; local melatonin; rat